Analisis Peningkatan Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Menggunakan Importance Performance Analysis dan Metode Quality Function Deployment - Thabrani, Gesit; Firman, Firman; Azmi, Nia Lailatul (Jurnal Kajian Manajemen Bisnis, 2017)
Competition increasingly competitive requires every company both manufacturing and services, including RSUD Pariaman to always consider the customer wants and needs and try to meet what they expect. The purpose of this research is to analyze how is the quality of service, a service attribute be the first priority, and recommendations can be given to improve the quality of services RSUD Pariaman. The results showed that 25 of the 26 attributes of service is worth the negative gap with the largest value of -1.21 for the attribute "The hospital has a waiting room, treatment rooms, beds, toilets and adequate sanitation" and â€œThe hospital has enough medicines and adequate medical equipment (such as CT-Scan, MRI, USG, etc)â€. Based on analysis of IPA there are 11 attributes included in quadrant A and must be repaired. Recommendations based on the highest priority needs to be done and improved in advance is "Conducting training and employee empowerment" with the highest analytical value 0.1702 or 17.02%. With this recommendation is expected to improve the quality of service in RSUD Pariaman. Â Keywords: Service Quality, Importance Performance Analysis, Quality Function Deployment